Homeschooling as an alternative to be questioned: problem and proposals (Práxis Educativa, 2019)
This study makes an analysis, from the historical perspective, of the processes that, in modernity, led to compulsory schooling. The main objective is to demonstrate aspects of the discussion, based on the present that intends to break with this obligation or, more specifically, the possibility of regulating homeschooling. For such, the methodological procedures involve the verification of the Brazilian legislation and the norms already issued on the subject. The dialogue established with the aforementioned theoretical framework prioritizes classic authors of the contemporary pedagogical debate, as well as advocates of schooling, in the face of attempts to disqualify its importance. It is concluded that the authorization of homeschooling, if done by the competent bodies, needs to be carefully accompanied by mechanisms to investigate what goes on in the family and how these children will learn and be socialized.Keywords: Schooling. Homeschooling. Educational legislation.